Relationship between Vitamin D Levels and Depressive Symptoms in Renal Transplant Recipients. (February 2014) - Ozkayar, Nihal; Altun, Bulent; Ulusoy, Semra; Yildirim, Tolga; Halil, Meltem; Yilmaz, Rahmi; Abudalal, Ayman; Altindal, Mahmut; Arici, Mustafa; Erdem, Yunus
Objective: Vitamin D deficiency might influence the development of depression; however, the association between vitamin D and depression in renal transplant recipients has not been evaluated. We aimed to test if there is a relation between 25-hydroxy (OH) vitamin D levels and depressive symptoms in patients with kidney transplantation. Methods: This was a cross-sectional and descriptive study. A total of 117 renal transplant recipients (44 female, 73 male; mean age, 39.0 ± 11.7 years) were included in the study. Patients were stratified to two groups according to the cut-off point (7) of depression subscale (D) of Hospital Anxiety Depression Scale (HADS), with or without depression risk. Blood biochemistry, glomerular filtration rate (GFR), and 25-OH vitamin D levels were determined. Results: Depression scores were higher than cut-off point in 33.3% ( n = 39) of patients. The mean 25-OH vitamin D level was 19.6 ± 12.0 µg/L. In the group with depression risk, 25-OH vitamin D levels were significantly lower than the other group (15.2 ± 9.2 µg/L and 21.9 ± 12.7 µg/L, respectively; p = 0.004). No significant difference was observed between the two groups in terms of demographic parameters, blood biochemistry, and GFR. A negative correlation was detected between HADS-D score and vitamin D levels ( r = −0.365, p < 0.0001). Conclusion: Lower serum 25-OH vitamin D levels are associated with higher depressive symptom levels among renal transplantation recipients. This finding should be the basis for further clinical studies and for future prospects on vitamin D supplementation for prevention and treatment of depression in these patients.